THE RUSSIA-UKRAINE WAR IN THE STUDY OF HISTORICAL LAW & CONFLICT OF STATE SECURITY AREA - Sergei, Grigori (International Journal of Law Reconstruction, 2022)
This study aims to provide an explanation of the history of the conflict between Russia and Ukraine during the reign of Vladimir Putin. Considering the Russo-Ukrainian conflict has become a war that is not only carried out by two countries, but many western countries interfere in this matter with their respective political goals. The conflict in Ukraine from the beginning was just the escape of Crimea from Ukraine to Russia, it was later followed by separatist efforts in other regions in Ukraine, in the eastern region which was also dominated by ethnic Russians. As a result, the US and NATO immediately sought to intervene to prevent the fall of Ukraine to Russia. So all the maneuvers of the US and NATO were immediately responded to by the maneuver of Russia deploying its troops and weapons on the Ukrainian border. The method used in this study applies quantitative methods with data collection techniques obtained from various literatures. The references used are literature studies on various books, newspapers, clippings, scientific journals, the internet, and other documentation that contains information about the conflict between Russia and Ukraine during the reign of Vladimir Putin in 2012 - 2018. The conclusions of this study is that Russian President Vladimir Putin claimed and emphasized that the act of sending Russian military forces to Ukraine and Crimea (NATO) is a form of Russian preparedness in case of violence and other things that can hurt Russian citizens who live in Ukraine and Crimea.